Performance analysis of an optical cross connect at DWDM system - Chowdhury, Afsana Ahmed; Nasarullah, Nafiza; Jabin, Iffat (BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2010.